Formative Assessment and Educational Benefits - Rosa Vegliante (Encyclopedia, 2025)
Evaluation in education is a complex and multifaceted process, linked to teaching and planning. It represents a powerful tool for regulating behaviors, refining actions, and adapting educational interventions to the specific context in which they are implemented. In this evaluation framework, the work aims to highlight the educational value of assessment, considered a moment in which both the teacher and the student are involved in the teaching-learning process. In particular, formative assessment allows you to find essential information to understand the progress of the actions implemented, highlighting strengths and weaknesses to intervene in educational planning. In this sense, it becomes a valid support for both teachers and students as it allows them to monitor the progress of the teaching/learning process. The work is divided into two parts: the first is theoretical, in which the transition from the assessment of learning (summative) to the assessment for learning (formative) is presented; the second is focused on formative assessment and feedback practices. From a methodological perspective, the literature review emphasizes the potential of assessment that involves students both as recipients and active participants through peer assessment. The paper highlights potential and challenges aimed at improving and experimenting with ways to enhance evaluation competence, which prepares students for professional life.